Prioritisation Assessment and Robust Predictive System for Medical Equipment: A Comprehensive Strategic Maintenance Management - Aizat Hilmi Zamzam; Ayman Khallel Ibrahim Al-Ani; Ahmad Khairi Abdul Wahab; Khin Wee Lai; Suresh Chandra Satapathy; Azira Khalil; Khairunnisa Hasikin; Muhammad Mokhzaini Azizan (Frontiers Media SA, 2024)
Indexed by WOS/Scopus/ERA